ANALISIS PROGRAM MINDFULNESS BERBASIS NILAI-NILAI PESANTREN DALAM MENGURANGI GEJALA DEPRESI PADA REMAJA - Ainurrafiq Dawam; Miftahul Khoir; Joko Supeno Mukti (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2024)
This study analysed Pesantren-based mindfulness program in reducing symptoms of depression among adolescent students at Pesantren Tahfidz Bustanul Qur'an Melawi, West Kalimantan. Using literature review this study provides a comprehensive overview of the program's impact. Primary data were obtained from related literature, including scientific journals, books, and previous research reports relevant to the topics of mindfulness, pesantren education, and adolescent mental health. The results of the study indicate that the program is effective in improving students' emotional regulation and psychological flexibility, ultimately contributing to reduced stress levels and depression symptoms. The program's advantage over similar mindfulness programs in general and other religious school settings is its deep integration with Islamic teachings, such as tawakkul (trust in God) and sabr (patience), which enhance the students' spiritual experience. These findings affirm that a holistic approach combining mental, emotional, and spiritual aspects in a mindfulness program can be an effective mental health intervention model in pesantren.